Formulation of Coalition Threshold For Political Parties Based on Proportionality Principles In The Presidential Election Post Constitutional Court Decision No. 62/PUU-XXII/2024 - Harimurti Adi Nugroho; O. Djunaedi; Ismail Ismail (Pelopor Publikasi Akademika, 2025)
This research aims to formulate a maximum threshold for political party coalition membership based on proportionality principles to prevent dominance. Research findings indicate that in Indonesia's positive legal system, particularly regarding presidential elections, there are no legal norms explicitly defining political party coalition dominance in presidential candidate nominations. Article 6A of the 1945 Constitution does not directly address this matter but implicitly regulates the limitation of absolute dominance through a